Analysis of Red Betel Leaf Tests As A Natural Anti-Infection In Post Partum Mothers - Yudhia Fratidhina; Sri Mulyati; Hetty Astri; Silvester Maximus (Women, Midwives and Midwifery, 2023)
Background: Incidence of infection contributes to maternal mortality. Innovative efforts to treat infection in postpartum mothers continue to be made, including non-pharmacological techniques. The local wisdom of red betel leaves is believed by the community to be able to handle it. The true efficacy of this extraordinary red betel leaf deserves further investigation. The purpose of this study was to assess the effectiveness of red betel on perineal wound healing in postpartum mothers.